2009
DOI: 10.1161/atvbaha.108.171298
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between P450 Eicosanoids and Nitric Oxide in the Control of Arterial Tone in Mice

Abstract: Objective-Epoxyeicosatrienoic acids (EETs) serve as endothelial-derived hyperpolarizing factors (EDHF), but may also affect vascular function by other mechanisms. We identified a novel interaction between EETs and endothelial NO release using soluble epoxide hydrolase (sEH) Ϫ/Ϫ and ϩ/ϩ mice. Methods and Results-EDHF responses to acetylcholine in pressurized isolated mesenteric arteries were neither affected by the sEH inhibitor, N-adamantyl-NЈ-dodecylurea (ADU), nor by sEH gene deletion. However, the EDHF resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 54 publications
11
115
2
Order By: Relevance
“…Incubation with specific calcium‐activated potassium channel inhibitors failed to attenuate the vasodilator effect of 11, 12‐EET in. This finding was similar to the results demonstrated by Hercule et al 34. in which the dilator responses to 5, 6‐EET, 11, 12‐EET and 14, 15‐EET were not changed due to apamin/ChTx in mouse mesenteric arteries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Incubation with specific calcium‐activated potassium channel inhibitors failed to attenuate the vasodilator effect of 11, 12‐EET in. This finding was similar to the results demonstrated by Hercule et al 34. in which the dilator responses to 5, 6‐EET, 11, 12‐EET and 14, 15‐EET were not changed due to apamin/ChTx in mouse mesenteric arteries.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it was proposed that stimulation of BK ca channel in vascular smooth muscle cells are not linked to the direct effects of EETs 33. Hercule et al 34. also reported that EDHF‐dependent relaxation in mouse mesenteric arteries was not prevented by iberiotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, the epoxyeicosatrienoic acids (EETs) produced from arachidonic acid are endothelial-derived hyperpolarizing factors that are associated with vasodilation and natriuresis 11,12 and may indirectly propagate vasodilation [13][14][15] by activating endothelial nitric oxide synthase. 16,17 EETs can be rapidly metabolized to dihydroxyeicosatrienoic acids (DHETs) by the enzyme soluble epoxide hydrolase (sEH), resulting in a concomitant loss of vasodilation. 18,19 sEH also converts the protoxins, epoxyoctadecenoic acids, to the dihydroxyoctadecenoic acids, which are potent cytotoxic and proinflammatory metabolites.…”
Section: July 2014mentioning
confidence: 99%
“…The sEH substrates, EETs, have known vasodilatory actions. [12][13][14][15][16][17][18][19]23 However, because of the short half-life of EETs, 33 these sEH substrates were below the level of detection and it was not . Schematic of proposed α-linolenic acid-induced alterations in the oxylipin profile.…”
Section: Downloaded Frommentioning
confidence: 99%
“…We performed radiotelemetry on adult male C57Bl6 and NZO mice (34 weeks) as outlined elsewhere. 28 BP devices were implanted in mice. After 10 days, mice had recovered from surgery and exhibited regular diurnal rhythms of activity.…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%